Dead set : [large type] an Amish cozy mystery - Chapman, Vannetta (Agatha's Amish B&B ;, 2022)
"It was supposed to be a simple remodel. Agatha Lapp is elated when Channel 4 News decides to run a feature story on Amish businesses. The cameras are rolling live when Agatha raises the rubber mallet and punches the first hole in her living room wall. That's when things get complicated . . . Hidden inside the wall is a diamond-studded belt buckle. With the help of a retired detective and her best friend, Agatha sets out to solve the mystery of the Lost Texas Treasures and find a killer. When she finds herself looking down the barrel of a gun, she's no longer worried about a remodel. She just wants to live through this showdown."--